The Effect of Learning Media, Facilitators, Learning Models and Training on Teacher Competency In In-Depth Learning Training in Sukoharjo District - Indah Nastiti; Istiatin Istiatin; Kartika Hendra TS (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of learning media, facilitators, learning models, and training on teacher competence in the Deep Learning Training Program in Sukoharjo Regency. This research employed a quantitative descriptive approach using a survey method. The population consisted of all participants of the Deep Learning Training Program for teachers in Sukoharjo Regency in 2025, totaling 103 teachers. The sampling technique used was a census method, in which the entire population was taken as the research sample. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 27. The results showed that learning media had a positive and significant effect on teacher competence with a t-value of 10.182 and a significance value of 0.000. Facilitators also had a positive and significant effect on teacher competence with a t-value of 7.693 and a significance value of 0.000. The learning model had a positive and significant effect on teacher competence with a t-value of 3.218 and a significance value of 0.002. Training likewise had a positive and significant effect on teacher competence with a t-value of 3.583 and a significance value of 0.001. Simultaneously, learning media, facilitators, learning models, and training significantly influenced teacher competence with an F-value of 138.373 and a significance value of 0.000. The coefficient of determination (Adjusted R Square) of 0.843 indicates that 84.3% of teacher competence is influenced by learning media, facilitators, learning models, and training, while the remaining 15.7% is influenced by other factors outside the scope of this study. Keywords: Learning Media, Facilitators, Learning Models, Training, Teacher Competence.